Outcomes from adult veno-arterial extracorporeal membrane oxygenation in a cardiovascular disease center from 2009 to 2019. (April 2022) - Gao, Sizhe; Liu, Gang; Yan, Shujie; Lou, Song; Gao, Guodong; Hu, Qiang; Zhang, Qiaoni; Qi, Jiachen; Yan, Weidong; Wang, Qian; Wang, Jian; Ji, Bingyang
Introduction: Extracorporeal membrane oxygenation (ECMO) is an imperative short-term cardiopulmonary support device now. We aimed to provide a single-center experience of veno-arterial (V-A) ECMO management and identify the risk factors of in-hospital mortality. Methods: We conducted a retrospective review of adult patients who received V-A ECMO between 2009 and 2019 in a cardiovascular disease center. The risk factor analysis of in-hospital mortality was conducted. Results: The study reviewed 236 patients, with an overall survival rate of 68.2%. The survivors' blood lactate concentration is significantly lower than non-survivors [7.4 (7.8) vs 11.1 (9.7), p  = 0.002]. Patients who received heart transplantation were with higher in-hospital survival rate. Survivors developed less hepatic dysfunction, acute kidney injury and myocardial damage [23 (14.3%) vs 19 (25.3%), p  = 0.039; 81 (50.3%) vs 51 (68%), p  = 0.011; 24 (14.9%) vs 22 (29.3%), p  = 0.009, respectively], with higher rate of continuous renal replacement therapy (CRRT) [56 (34.8%) vs 53 (70.7%), p  < 0.001]. Fewer survivors' 24 hours and total chest drainage was over 1000 mL, and the rate of re-exploration as well as red blood cell and platelet transfusion were lower in survivors. In multivariate analysis, female, pre-ECMO blood lactate concentration, hyperlipidemia, CRRT, and 24 hours chest drainage ⩾ 1000 mL were risk factors of early mortality. Conclusions: By providing a general description of V-A ECMO practice at a single-center in China. Post-heart transplant graft failure was associated with numerically, the greatest survival in our practice. Furthermore, female sex, pre-ECMO blood lactate concentration, hyperlipidemia, CRRT, and high blood loss in chest drains are predictors of mortality in patients who undergo V-A ECMO.